2005
DOI: 10.1111/j.1464-5491.2005.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal erythrocyte membrane lipids modification: preliminary observation of an early sign of compromised insulin sensitivity in offspring of gestational diabetic women

Abstract: The altered plasma and erythrocyte fatty acids in the cord blood of babies born to women with gestational diabetes suggests a perturbation in the maternal-fetal nutrient transport and/or fetal lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…In our previous communications, we reported that red cells of women with GDM at diagnosis (25), and plasma (24) and red cells (23) of their neonates at birth, had an abnormal FA composition. The two questions that arose from these studies were the following: (i) Is the abnormality a generalized phenomenon, or is it restricted to red cells of the mothers with GDM and plasma and red cells of their newborn babies?…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our previous communications, we reported that red cells of women with GDM at diagnosis (25), and plasma (24) and red cells (23) of their neonates at birth, had an abnormal FA composition. The two questions that arose from these studies were the following: (i) Is the abnormality a generalized phenomenon, or is it restricted to red cells of the mothers with GDM and plasma and red cells of their newborn babies?…”
Section: Discussionmentioning
confidence: 98%
“…Compared with healthy controls, the women with GDM had lower AA and DHA levels in red cells (25) but not in plasma (26). Because the maternal plasma AA and DHA, which is the main source for the fetus, was normal in the women with GDM, it is unclear whether the observed compromise in the level of the two FA in the neonates (23,24) was due to reduced supply, impaired transfer, or both. The aim of this study was to investigate whether GDM alters the placental FA profile.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In another study carried out in London, significantly lower ALA and higher AA in plasma CPG fraction was found in diabetic mothers than in healthy controls at delivery (Min et al, 2005b). However, AA was significantly lower in erythrocyte membrane PC fraction.…”
Section: Fatty Acid Supply During Pregnancy In Women With Gestationalmentioning
confidence: 92%
“…This altered glucose control may also have a negative impact on fetal LCPUFA accretion. Min et al (Min et al, 2005b) investigated cord blood samples of newborns from mothers with and without GDM in London and found significantly decreased ALA, LA, DHA and AA values in the plasma TG fraction. In contrast, in the plasma CPG fraction only DHA values were significantly lower in the diabetic group.…”
Section: Fatty Acid Supply In Newborns Of Mothers With Gestational DImentioning
confidence: 99%